ANALYSIS OF THE BACKGROUND LEVEL OF M1 AND M2 MACROPHAGE CYTOKINES IN PATIENTS WITH REVISION RHINOPLASTY - Zhuravel, O.Yu.; Zaporozhets, T.Yu.; Khrapach, V.V. (World of Medicine and Biology, 2024)
The purpose of the study was to evaluate the background level of cytokines M1 and M2 of the macrophage phenotype in patients with revision rhinoplasty. The search for effective diagnostic methods will improve treatment and prevention of negative consequences of reconstructive rhinoplasty. 63 patients (18–45 years old) who underwent revision rhinoplasty using a rib graft were under supervision. Patients were divided into two groups based on fibrinogen levels for further studies. The levels of TNF-α, TGF-β1 cytokines (DRG Diagnostic Inc., Germany), IL-6, IL-10, IL-13 (IBL International, Germany), IL-12, IL-18 (ElabScience, USA) were evaluated in all patients. In patients after rhinoplasty who have postoperative complications in the form of nasal deformity, there was an increase in the synthesis of cytokines characteristic of macrophages of the M1 phenotype and a decrease in the level of cytokines of the M2 phenotype of macrophages. The identified differences require further research to study their pathogenetic role in developing complications in rhinoplasty patients.